Diet Composition and Overlap of Two Mesocarnivores, Leopard Cat (Prionailurus bengalensis) and Javan Mongoose (Urva javanica), in Java, Indonesia - Sena Adi Subrata; Ulfah Darmayani Permatasari (HAYATI Journal of Biosciences, 2023)
Dietary study of carnivores has garnered a great deal of attention for a very long time since it provides information for comprehending ecological processes and tracking the economic effects of animals on food production. Few studies reported alternative prey that is detrimental to food production, such as rodents and insects, in addition to the numerous studies on livestock predation. Therefore, this study aims to provide information on the diet composition and overlap of two mesocarnivore species, Javan mongoose (Urva javanica) and leopard cat (Prionailurus bengalensis), in Java, Indonesia. The macroscopic observation technique was applied for identifying food remnants found in the 90 feces of the mongoose and 100 feces of the cat collected in 2018. Twenty three and 21 taxa of prey were found in the leopard and Javan mongoose feces. Rodentia was the most frequent taxa found in the feces of both species, followed by Galliformes. Insects comprised the majority of diet items but at low frequencies. Two mesocarnivores were specialists (Levin’s index of leopard cat: 0.08; Javan mongoose: 0.26) with fairly high diet overlap (Pianka’s index = 0.78). The results provided compelling evidence of the positive and negative impacts of mesocarnivores on food production in Java.